Pertanggungjawaban Direksi dalam Penerapan Prinsip Fiduciary Duty atas Penerbitan Faktur Pajak Secara Fiktif: Studi Putusan Mahkamah Agung Nomor 3343 K/Pid.Sus/2019 - Jordi Viero; Ningrum Natasya Sirait; hasim purba (Jurnal Hukum Lex Generalis, 2026)
The Board of Directors of a Limited Liability Company is obligated to manage the company based on the principle of fiduciary duty, encompassing good faith, prudence and legal compliance. The issuance of fictitious tax invoices as a means of VAT avoidance constitutes a clear violation of this principle, giving rise to personal liability of the directors in both civil and criminal law. However, in Supreme Court Decision Number 3343 K/Pid.Sus/2019, the judge's considerations focused primarily on fulfilling the elements of tax criminal offenses without explicitly linking the fiduciary duty principle as the basis for directors' liability, thus necessitating a stronger integration between corporate law and tax criminal law regimes comprehensively.